Association Between Postoperative Dexmedetomidine Use and Arrhythmias in Infants After Cardiac Surgery. Issue 4 (July 2019) - Ortmann, Laura A.; Keshary, Meera; Bisselou, Karl Stessy; Kutty, Shelby; Affolter, Jeremy T.
Background: Dexmedetomidine has been suggested as an arrhythmia prophylactic agent after surgery for congenital heart disease due to its heart rate lowering effect, though studies are conflicting. We sought to study the effect of dexmedetomidine in infants that are at highest risk for arrhythmias. Methods: Retrospective cohort study of infants less than six months of age undergoing cardiopulmonary bypass for congenital heart disease. The arrhythmia incidence in the first 48 hours after surgery in infants receiving dexmedetomidine for sedation was compared to those that did not receive dexmedetomidine. Results: A total of 309 patients were included, 206 patients who did not receive dexmedetomidine and 103 patients who did. The incidence of tachyarrhythmias was similar between the non-DEX group and the DEX group (19% vs 15%, P = .34). When adjusted for baseline differences, the non-DEX group did not have an increased risk of postoperative tachyarrhythmias (odds ratio [OR]: 1.4, 95% confidence interval [CI]: 0.5-3.8). The non-DEX group had an increased need for treatment for arrhythmias (18% vs 8%, P = .012). The three lesions with baseline higher risk for arrhythmias (tetralogy of Fallot, transposition of the great arteries, and complete atrioventricular canal) had an increased incidence of tachyarrhythmias in the non-DEX group (34% vs 6%, P = .027). This risk was not significant in multivariate analysis (OR: 2.5, 95% CI: 0.4-15.5). Conclusions: High-risk infants had decreased incidence of tachyarrhythmias when receiving dexmedetomidine, though this was not significant after accounting for baseline differences between groups.